DETERMINATION ZIRCONIUM WITH THE SOLUTION OF 1 - (2-HYDROXY-1-NAPHTHOYAZO)-2-NAPHTHOL-4-SULFATE - Kutlimurotova, Nigora; Tursunqulov , Jasur; Jalilov , Fazliddin; Rahimov , Samariddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: New methods for spectrophotometric determination of zirconium have been developed. The 1 - (2-hydroxy-1-naphthoyazo)-2-naphthol-4-sulfate was selected as the analytical reagent. Influence of pH, time and amound of reagent in obtaining complex zirconium has been studied. The dependence of the analytical signal on the concentration of analytes is linear in the range from 2.0–100.0 μg.